2000
DOI: 10.1042/bj3450687
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of morphine dehydrogenase and stabilization against covalent inactivation

Abstract: Morphine dehydrogenase (MDH) of Pseudomonas putida M10 catalyses the NADP(+)-dependent oxidation of morphine and codeine to morphinone and codeinone. This enzyme forms the basis of a sensitive detection and assay method for heroin metabolites and a biotransformation process for production of hydromorphone and hydrocodone. To improve these processes we have undertaken a thorough examination of the kinetic mechanism of MDH. Sequence comparisons indicated that MDH belongs within the aldose reductase enzyme family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Furthermore, MDH became inactivated by morphinone through the formation of a covalent adduct with Cys80, and it was found that changing this residue to a serine greatly enhanced the stability of MDH (25). A mutation, K244M, leading to an approximately 10-fold-lessactive MDH was combined with the C80S mutation, to give morA C80S ⅐ K244M (25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, MDH became inactivated by morphinone through the formation of a covalent adduct with Cys80, and it was found that changing this residue to a serine greatly enhanced the stability of MDH (25). A mutation, K244M, leading to an approximately 10-fold-lessactive MDH was combined with the C80S mutation, to give morA C80S ⅐ K244M (25).…”
Section: Resultsmentioning
confidence: 99%
“…A 1.2-kb PstI fragment bearing the mutant morA gene complete with its upstream ribosome binding site and promoter sequences was excised from pMDH1.7 (25) and ligated into PstI-digested ps 1EMBL (21). This resulted in the construct pMORA4C80S ⅐ K244M, which contained suitable restriction sites for further subcloning.…”
Section: Chemicals and Other Materials Nadh Nadph Nadmentioning
confidence: 99%
See 1 more Smart Citation
“…It is this proR hydride that is transferred to the substrate, as has been shown by studies with labelled cofactor. 28 Sequence similarity of AKR5H1 to that of other mycobacterial AKRs and putative orthologues from the Corynebacterineae In order to gain insight into the functional role of AKR5H1, we compared the sequence of AKR5H1 to those of its orthologues from the closely related mycobacterial species M. tuberculosis and Mycobacterium leprae and from other representatives of the suborder Corynebacterineae, Nocardia farcinica and Corynebacterium glutamicum (Fig. 5).…”
Section: Comparison Of the Cofactor-binding Site Of Akr5h1 To That Ofmentioning
confidence: 99%
“…Bacterial transformations of the morphine have also been reported with the strains Arthrobacter sp. [14], Pseudomonas testosteroni [15], Pseudomonas putida M10 [16,17], Bacillus sp. [18], Mycobacterium neoaurum MTP650 [19], and Streptomyces griseus NRRL B8090 [20].…”
Section: Introductionmentioning
confidence: 99%